Significant Decline in Child Marriage Rates in Indonesia By 2025: The Central Role of Guidance for School-Age Youth Following Law No. 16 Of 2019 - Nafhani, Ahmad; Maulida, Yulianiva; Aulia Raden , Andi Nur Fikriana; Septiana, Yunita Dewi; Fithrian Luthfan, Gusti Fadhil (Tasyri' : Journal of Islamic Law, 2026)
By 2025, Indonesia will have achieved a monumental milestone in child protection efforts with a significant decline in national child marriage rates. This success is the result of the strategic implementation of Law No. 16 of 2019, which sets the minimum marriage age at 19 years for both men and women. This study highlights how this decline was not only driven by regulatory changes but was critically accelerated by the effectiveness of the School-Age Youth Guidance Program (BRUS), which was widely promoted. This guidance method has become the primary tool in translating the mandate of the law into behavioral and social norm changes at the grassroots level. Through a structured psychoeducational approach within the school environment, the BRUS program has successfully increased adolescents' awareness of the negative impacts of child marriage on reproductive health, economic potential, and educational continuity. Additionally, this guidance equips adolescents with life skills, resilience, and the ability to make responsible decisions. Collaboration between educational institutions, local governments, and civil society organizations in implementing BRUS ensures broad reach and content relevant to the local context. As a result, there has been a paradigm shift among adolescents, parents, and community leaders, who now view delaying marriage age as an important investment for the future of the next generation. The drastic decline in child marriage rates by 2025 is clear evidence that the combination of progressive legal reforms and targeted educational interventions is key to ending the practice of child marriage in Indonesia.